Cerebral Amyloid Angiopathy and the Risk of Hematoma Expansion. Issue 6 (27th August 2022) - Seiffge, David J.; Polymeris, Alexandros A.; Law, Zhe Kang; Krishnan, Kailash; Zietz, Annaelle; Thilemann, Sebastian; Werring, David; Al‐Shahi Salman, Rustam; Dineen, Robert A.; Engelter, Stefan T.; Bath, Philip M.; Sprigg, Nikola; et al.
Abstract : Objective: We assessed whether hematoma expansion (HE) and favorable outcome differ according to type of intracerebral hemorrhage (ICH). Methods: Among participants with ICH enrolled in the TICH‐2 (Tranexamic Acid for Hyperacute Primary Intracerebral Haemorrhage) trial, we assessed baseline scans for hematoma location and presence of cerebral amyloid angiopathy (CAA) using computed tomography (CT, simplified Edinburgh criteria) and magnetic resonance imaging (MRI; Boston criteria) and categorized ICH as lobar CAA, lobar non‐CAA, and nonlobar. The main outcomes were HE and favorable functional outcome. We constructed multivariate regression models and assessed treatment effects using interaction terms. Results: A total of 2, 298 out of 2, 325 participants were included with available CT (98.8%; median age = 71 years, interquartile range = 60‐80 years; 1, 014 female). Additional MRI was available in 219 patients (9.5%). Overall, 1, 637 participants (71.2%) had nonlobar ICH; the remaining 661 participants (28.8%) had lobar ICH, of whom 202 patients had lobar CAA‐ICH (8.8%, 173 participants according to Edinburgh and 29 participants according to Boston criteria) and 459 did not (lobar non‐CAA, 20.0%). For HE, we found a significant interaction of lobar CAA ICH with time from onset to randomization (increasing risk with time, p interaction  < 0.001) and baseline ICH volume (constant risk regardless of volume, p interaction  < 0.001) but no association between type of ICH and risk of HE or favorable outcome. Tranexamic acid significantly reduced the risk of HE (adjusted odds ratio = 0.7, 95% confidence interval = 0.6–1.0, p  = 0.020) without statistically significant interaction with type of ICH ( p interaction  = 0.058). Tranexamic acid was not associated with favorable outcome. Interpretation: Risk of HE in patients with lobar CAA‐ICH was not independently increased but seems to have different dynamics compared to other types of ICH. The time window for treatment of CAA‐ICH to prevent HE may be longer. ANN NEUROL 2022;92:921–930